2022
DOI: 10.1038/s41598-022-24653-0
|View full text |Cite
|
Sign up to set email alerts
|

Ecological study of ambient air pollution exposure and mortality of cardiovascular diseases in elderly

Abstract: As an independent risk factor, ambient air pollution can assume a considerable part in mortality and worsening of cardiovascular disease. We sought to investigate the association between long-term exposure to ambient air pollution and cardiovascular disease mortality and their risk factors in Iranian's elderly population. This inquiry was conducted ecologically utilizing recorded data on cardiovascular disease mortality from 1990 to 2019 for males and females aged 50 years or more from the Global Burden of Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 94 publications
1
3
0
Order By: Relevance
“…In the present study, we found that PM 2.5 and PM 10 were the most important variables affecting multiple maternal blood markers. Similar results were also observed in previous studies that chronic exposure to higher levels of air pollutants (PM 1 , PM 2.5 , PM 10 , and NO 2 ) was associated with increased platelet size (Hou et al 2020 ), and in addition to systemic inflammation (Ferrucci and Fabbri 2018 ), the pro-thrombotic pathway induced by particulate PM may also be an important biological pathway contributing to cardiovascular risk (Brook and Rajagopalan 2010 ; Dehghani et al 2022b ; Rajagopalan et al 2018 ). Results from rodent model studies suggest that exposure to airborne PM may lead to platelet aggregation and arterial thrombosis (Hadei and Naddafi 2020 ).…”
Section: Resultssupporting
confidence: 88%
“…In the present study, we found that PM 2.5 and PM 10 were the most important variables affecting multiple maternal blood markers. Similar results were also observed in previous studies that chronic exposure to higher levels of air pollutants (PM 1 , PM 2.5 , PM 10 , and NO 2 ) was associated with increased platelet size (Hou et al 2020 ), and in addition to systemic inflammation (Ferrucci and Fabbri 2018 ), the pro-thrombotic pathway induced by particulate PM may also be an important biological pathway contributing to cardiovascular risk (Brook and Rajagopalan 2010 ; Dehghani et al 2022b ; Rajagopalan et al 2018 ). Results from rodent model studies suggest that exposure to airborne PM may lead to platelet aggregation and arterial thrombosis (Hadei and Naddafi 2020 ).…”
Section: Resultssupporting
confidence: 88%
“…Previously, mixed results have been found regarding the relationship between O 3 exposure and cardiovascular outcomes. For example, ecological study suggested a positive correlation between exposure to ambient O 3 and mortality of cardiovascular disease among the elderly in the Middle East [ 50 ], and several recent large cohort studies in the US and China showed that long-term exposure to O 3 was positively and monotonically related to cardiovascular mortality [ 5 , 51 , 52 ], whereas null or even negative associations were also reported in cohorts from France, Denmark, and the UK [ 53 55 ]. Since hypertension is one of the most important risk factors for various cardiovascular outcomes, the non-linear shape of the relationship between O 3 exposure and hypertension might indicate the presence of non-linear associations between O 3 exposure and other cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution's effects can be severe, including respiratory problems, cardiovascular disease, and premature death. The problem of protecting and restoring the environment is currently the main one of the essential tasks of science, the development of which is stimulated in all countries of the world [1]. Accurate measurement of air pollution is crucial for understanding the extent of the problem and developing effective control strategies.…”
Section: Dariya Bissengaliyevamentioning
confidence: 99%